Turtles [videorecording (DVD)] - Gourmet, Olivier; Johns, Dave, 1955-; Poupart, Brigitte (Darkstar Pictures, 2024)
Thom and Henri met 35 years ago, and their love has never faltered. Their seemingly perfect life begins to go awry when Henri retires from being a police officer. Now, Henri's days become long, each one as bland as the next, while his feelings for Thom are fading fast. They drift away from each other a little more each day. Thom's love for Henri remains strong though and he is not ready to give up. He will do anything to rekindle their love, even if that means asking Henri for a divorce.